Src and fibroblast growth factor 2 independently regulate signaling and gene expression induced by experimental injury to intact articular cartilage. Issue 2 (28th January 2013) - Watt, Fiona E.; Ismail, Heba M.; Didangelos, Athanasios; Peirce, Matthew; Vincent, Tonia L.; Wait, Robin; Saklatvala, Jeremy
Abstract: Objective: To investigate whether cartilage injury activates protein tyrosine kinases distinct from fibroblast growth factor (FGF)–related signaling, and whether they contribute to injury‐induced gene responses. Methods: Phosphokinases and protein tyrosine phosphorylation were assayed by Western blotting of cartilage lysates. Immunoprecipitation and Western blotting with 4G10 antibody and immunoprecipitation kinase assay were carried out. Tyrosine‐phosphorylated proteins on silver‐stained gels of injured cartilage lysates were identified by mass spectrometry. Messenger RNA induction in cartilage explants was assessed by quantitative reverse transcriptase–polymerase chain reaction. Results: Protein tyrosine phosphorylation occurred within seconds of injury to the surface of intact articular cartilage, as did activation of MAPKs and IKK. Activation did not reoccur upon reinjury of cultured explants. The prominent tyrosine‐phosphorylated proteins focal adhesion kinase, paxillin, and cortactin were identified as substrates of Src family kinases. The Src family kinase inhibitor PP2 blocked injury‐induced tyrosine phosphorylation. It did not prevent activation of the MAPKs and IKK but differentially inhibited 8 of 10 inflammatory response genes that were induced by injury. In contrast, FGF signaling blockade with PD173074 reduced all MAPK and IKK activation by ∼50% and inhibited a different subset of genes but had no effect on Src‐like signaling. Conclusion: Injury to the surface of intact articular cartilage activates Src‐like kinases as well as MAPKs and IKK (implying NF‐κB activation). FGF‐2 contributes to MAPK/IKK activation but not to Src‐like signaling, suggesting that the latter is a parallel pathway that also regulates the injury‐induced inflammatory gene response.